Coping Strategies of University EFL Teachers for Online Instruction during COVID-19 in Nepal - Rai, Prakash (Journal of NELTA, 2022)
This paper aims at exploring the perceptions, and practices of University EFL teachers in Nepal, particularly the challenges found and strategies adopted to deal with teaching English through online instruction during the pandemic. The in-depth unstructured interview as a research tool under narrative inquiry has been employed to collect the data while the concept of thematic analysis by Riessman has been exploited to analyze and interpret the collected data. The research ﬁnding reveals that despite technological inefﬁciency, social barriers, and psychological fear teachers underwent through the initial phase, the subsequent online classes with some of the coping strategies such as self-initiation, self-discovery, and cooperative approach have been found profoundly effective and productive both for EFL teachers and students. It also is found that online classes truly materialized the theoretical idea-ELT with ICT into the application to make English language teaching proceed ahead with IT. Such classes in EF during the pandemic lockdown forcefully shifted the paradigm of teaching from chalk-and-talk instructor-centered to a digtal interactive learner-centered.